Benefits of using Esports as a wellness activity in colombian high education institutions - Estacio, Camilo
This article is part of a research that pretended to establish the benefits of using competitive video games as Student Services activities for higher education students. In order to run this research, first it was necessary to locate literature explaing the benefits of video games for its users, and documentation on the use of eSports in university environments. For this, after doing a search for universities using eSports, the Student Services managers of four of the contacted institutions were interviewed. This article presents the results of the interviews, hoping they will be useful to those who is writing eSports project in a high school or university.